KAJIAN DAS AIR DINGIN DITINJAU DARI PERUBAHAN TUTUPAN LAHAN TAHUN 2008 - 2021 - Muhammad Fajri; Hary Febrianto; Novelisa Suryani (Jurnal Azimut, 2022)
This research was conducted in the Air Dingin watershed of West Sumatra which aim calculating changes of land cover area in Air Dingin watershed (2008 – 2021). To determine land cover changes using maximum likelihood classification by utilizing Arc Map 10.8. It can classify land cover change and Microsoft Excel software to calculate land cover change. The result shows that the landcover change of Air Dingin Watershed in 2008 - 2021 largest increase in the shrub area by 392.60 ha (3.1%) and followed by dry land agriculture which increased 215.18 ha (1.7 %), building area increased by 148.68 ha (1.2%), mixed gardens by 16.94 ha (0.1%). The increase in land area will be followed by a reduction in land cover, which has the largest decrease in forest area, namely 635.58 ha (5.0%), followed by a decrease in paddy fields of 129.25 ha (1.0%) , waters decreased by 8.57 ha (0.1%).